Україна удосконалює правове регулювання медіа у відповідь на безпекові загрози і вимоги як до країни-кандидата в члени ЄС - Джолос, Олег Володимирович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
On March 31, 2023, the Law of Ukraine “On Media” No. 2849-IX entered into force. Its approval is one of the criteria necessary for the start of negotiations on Ukraine’s accession to the EU. Granting Ukraine the status of a candidate for membership of the European Union, the European Commission recommended that our country “combat the influence of private interests by adopting a law on the media industry, which brings Ukrainian legislation into line with the EU Directive on audiovisual media services and empowers an independent media regulator.” At the same time, the large-scale invasion of Russia, which is accompanied by a powerful information war, propaganda and disinformation on the part of the aggressor, contributed to the adoption of the law “On Media” to no small extent. And only then – its inclusion in the list of requirements of the European Union in connection with Ukraine receiving candidate status. The European integration path is important and necessary for Ukraine, but modern security challenges, including in the information sphere, are now a matter of the survival of the state and our final victory in the war.